2014
DOI: 10.1002/lsm.22244
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed versus continuous wave CO2 laser excisions of 100 oral fibrous hyperplasias: A randomized controlled clinical and histopathological study

Abstract: Excision of fibrous hyperplasias performed with a CO2 laser demonstrated a good clinical outcome and long-term predictability with a low risk of recurrence regardless of the laser mode (cf or cw) used. Scarring after 6 months was only seen in 50.6% of the cases and was slightly more frequent in the cf mode group. Based on the findings of the present study, a safety border of 1 mm appears sufficient for both laser modes especially when performing a biopsy of a suspicious soft tissue lesion to ensure a proper hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…This shift was independent of the duration of the single CO 2 laser shot. Thus, the ablation of genetically encoded fluorescence in the green visible light range by a CO 2 laser occurred within the spatial range of collateral thermal damage in patients which lies on average between 150 and 160 μm …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shift was independent of the duration of the single CO 2 laser shot. Thus, the ablation of genetically encoded fluorescence in the green visible light range by a CO 2 laser occurred within the spatial range of collateral thermal damage in patients which lies on average between 150 and 160 μm …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the ablation of genetically encoded fluorescence in the green visible light range by a CO 2 laser occurred within the spatial range of collateral thermal damage in patients which lies on average between 150 and 160 μm. 13,14 To analyze a fluorophore in the NIR range, spheroids were stained with the anti-CD44v6 antibody BIWA conjugated to the NIR dye IRDye800CW. Spheroids were then cut with a scalpel or burned with a CO 2 laser (Figure 2A).…”
Section: Stability Of Fluorophores After Co 2 Laser Treatmentmentioning
confidence: 99%
“…3 The laser beam in PW has shown reduced thermal damage compared to CW in many animal studies. [25][26][27][28] In a clinical study, the thermal damage outcomes following excision biopsy of 100 fibrous hyperplasia lesions using CO 2 laser in PW and CW mode were compared. It was concluded that both laser modes produced similar thermal damage, and researchers recommended adding a 1 mm safety margin, especially in suspicious soft tissue lesions.…”
Section: Discussionmentioning
confidence: 99%
“…All included patients were allocated at random with a computer model to group 1, case (application of PRGF-ENDORET after surgery), or group 2, control (traditional hemostasis). 3 The local ethics committee approved the clinical protocol used for the study.…”
Section: Patient Selection and Study Designmentioning
confidence: 99%
“…Regular dental care with appropriate cleansing and disinfection measures, limitation of denture use to shorter periods, regular revision or adjustment of dentures, and if required, reconstruction of new prostheses, may prevent DIFH. 3 These lesions are very variable in shape and dimension, especially regarding the site of development and the duration of lesion evolution. It is a painless lesion.…”
mentioning
confidence: 99%